Uranium and thorium in the Precambrian basement of western Canada. II. Petrologic and tectonic controls - Burwash, R. A. (Canadian Journal of Earth Sciences, 1979)
Analyses of 182 basement cores, when plotted as log U and log Th, show bimodal frequency distributions. Cumulative frequency plots indicate an approximate 35–65% split between the two populations. Histograms of numbers of samples in various rock classes vs. log U fail to explain the bimodal distribution.A plot of log K vs. log U provides easy visual separation of rocks with varying K/U ratios and U contents. K/U values greater than 3 × 10 4 are ascribed principally to granulite facies metamorphism. K/U values less than 5 × 10 3 represent U-enrichment either in granitic melts or K-metasomatized gneisses. Factor analysis indicates a strong correlation between U, Th. Rb, Pb, and K.The geographic distribution of samples with K/U values greater than 3 × 10 4 can be related to relict Kenoran granulite facies terranes in the subsurface of northeastern Alberta and west central Saskatchewan similar to those mapped on the exposed Shield in northwestern Saskatchewan. These relict granulites could account for most of the samples in the smaller of the two sample populations.The U-enriched rocks are concentrated in three areas: (1) the epizonal, porphyritic granitic plutons of southwestern Saskatchewan, (2) linear quartz monzonite batholiths along the Kasba Lake – Edmonton gravity low, and (3) K-rich gneisses in the Peace River High of northwestern Alberta. In none of these areas is assimilation of large volumes of Aphebian sedimentary rocks indicated.